Flooding Regime Impacts on Radiation, Evapotranspiration, and Latent Energy Fluxes over Groundwater-Dependent Riparian Cottonwood and Saltcedar Forests. (16th November 2015) - Cleverly, James; Thibault, James R.; Teet, Stephen B.; Tashjian, Paul; Hipps, Lawrence E.; Dahm, Clifford N.; Eamus, Derek
Abstract : Radiation and energy balances are key drivers of ecosystem water and carbon cycling. This study reports on ten years of eddy covariance measurements over groundwater-dependent ecosystems (GDEs) in New Mexico, USA, to compare the role of drought and flooding on radiation, water, and energy budgets of forests differing in species composition (native cottonwood versus nonnative saltcedar) and flooding regime. After net radiation (700–800 W m −2 ), latent heat flux was the largest energy flux, with annual values of evapotranspiration exceeding annual precipitation by 250–600%. Evaporative cooling dominated the energy fluxes of both forest types, although cottonwood generated much lower daily values of sensible heat flux (<−5 MJ m −2  d −1 ). Drought caused a reduction in evaporative cooling, especially in the saltcedar sites where evapotranspiration was also reduced, but without a substantial decline in depth-to-groundwater. Our findings have broad implications on water security and the management of native and nonnative vegetation within semiarid southwestern North America. Specifically, consideration of the energy budgets of GDEs as they respond to fluctuations in climatic conditions can inform the management options for reducing evapotranspiration and maintaining in-stream flow, which is legally mandated as part of interstate and international water resources agreements.